Reducing Anxiety Through Education: A Systematic Review of Health Education for Hospitalized Tuberculosis Patients - Rizal, Imam Kurniawan; Waluyi=o, Agung; Maria, Riri; Yona, Sri (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2025)
Anxiety is a common psychological issue experienced by patients undergoing hospitalization, particularly those diagnosed with tuberculosis (TB), due to prolonged treatment periods and fear of stigma. As much as health education has been proposed as a potential intervention, research conducted so far is limited and varies in study methodology, and thus it's difficult to make conclusions. Further, there is no synthesized evidence regarding the impact of formal health education on anxiety among hospitalized TB patients, particularly where there is cultural diversity. This study aims to review the effect of health education interventions on anxiety levels in TB patients. A systematic review was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Literature was identified through PubMed, Scopus, and ProQuest databases. Inclusion criteria: RCTs or quasi-experimental studies involving pulmonary TB patients, evaluating the effect of health education on anxiety compared to other psychological interventions. Fifteen articles met the eligibility criteria and were included for analysis. The reviews summarized between 2019 and 2024 consistently showed that health education significantly reduces anxiety in hospital-admitted TB patients. This review update encapsulates the up-to-date evidence, expanding on the earlier work by adding recent evidence, mentioning varied forms such as single sessions, multimedia gadgets, and culturally sensitive materials. The findings highlight the importance of integrating health education as part of comprehensive TB care to address psychological distress and improve treatment outcomes.